PLGA nanoparticles augmented the anticancer potential of pentacyclic triterpenediol in vivo in mice. Issue 78 (5th August 2016) - Dubey, Ravindra Dhar; Saneja, Ankit; Qayum, Arem; Singh, Amarinder; Mahajan, Girish; Chashoo, Gousia; Kumar, Amit; Andotra, Samar S.; Singh, Shashank K.; Singh, Gurdarshan; Koul, Surinder; Mondhe, Dilip M.; et al.
Abstract : A novel pentacyclic triterpenediol (TPD), an anticancer lead from Boswellia serrata, was encapsulated into PLGA nanoparticles, leading to enhancement in anticancer potential in EAT bearing mice model. Abstract : A pentacyclic triterpenediol (TPD) from Boswellia serrata exhibited a good anticancer potential preclinically, however, it has low aqueous solubility and high lipophilicity, which therefore, necessitate suitable formulation development for in vivo application. In the present study TPD-loaded PLGA nanoparticles (TPD NPs) were prepared by an emulsion–diffusion–evaporation technique which exhibited an average particle size in the order of about 161 nm as confirmed by dynamic light scattering (DLS) and atomic force microscopy (AFM). The thermal analysis confirms that the TPD was entrapped into the NPs in an amorphous form. In vitro cell culture experiments indicated higher cellular cytotoxicity of the TPD-loaded NPs over free TPD in MCF-7 and OVCAR-5 cells. The higher cytotoxicity of TPD NPs was attributed to enhanced cellular apoptosis, loss of membrane potential and generation of high reactive oxygen species (ROS). The TPD-loaded NPs demonstrated a significantly higher in vivo anticancer potential as compared to TPD solution in the Ehrlich ascites tumor (EAT) model following intraperitoneal administration. Furthermore, no hematological and biochemical toxicity in EAT bearing mice was observed after the treatment. The results showed that the developed PLGA-NPs could be a potential option for improved TPD delivery in cancer chemotherapy.